Natounisarokerta on the Kapros. New Numismatic Evidence from the British Museum - Marciak, Michał (Anabasis. Studia Classica et Orientalia, 2013)
This paper examines local bronze coinage attributed to Adiabene (frequently and wrongly labeled as “Natounia coins”). It provides the first ever analysis of another item stored in the British Museum (including photographs). The paper rejects Milik’s identification of the ethnonym Natunia in coin legends, and instead suggests the following toponym: Natunisarokerta (as tentatively suggested by Le Rider). The meaning of this toponym is to be understood in the light of the Hatra inscription no. 21: built (ker) by [in the sense: on behalf of the kingdom of] Adiabene (Adiabene =natunissar, “given by Ishtar”, being another Semitic name for Adiabene).